Characteristics of the obesogenic environment around schools are associated with body fat and low-grade inflammation in Brazilian children - Mariana De Santis Filgueiras; Milene Cristine Pessoa; Josefina Bressan; Aline Siqueira Fogal Vegi; Ariene Silva do Carmo; Fernanda Martins de Albuquerque; Danielle Soares Gardone; Juliana Farias de Novaes (Public Health Nutrition, 2023)
Abstract